The Scattering and Neutrino Detector at the LHC - Navarria, Francesco (SciPost physics proceedings, 2025)
SND@LHC is a compact experiment that will detect high energy neutrinos produced by heavy flavour quarks at the LHC in the pseudo-rapidity region 7.2 < η < < η < 8.6. It is an hybrid system, comprising nuclear emulsions and electronic detectors, that allows all three ν ν flavours to be distinguished, thus opening an unique opportunity to probe the physics of charm production in the very forward region. The first phase aims at operating the detector throughout LHC Run 3 collecting a total of 150 fb ^{-1} − 1 . The electronic subdetectors were assembled in the summer and recently operated in test beams.